PENGARUH PERTUMBUHAN PENJUALAN, RISIKO BISNIS, DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yan Irianis; Dwi Eriyanto; Syahrul Syahrul; Sarpan Sarpan (JURNAL MITRA MANAJEMEN, 2023)
The purpose of the study with the title of the effect of sales growth, business risk, and asset structure on capital structure in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange is to find out how big (a) the influence of sales growth on capital structure, (b) the effect of business risk on capital structure, (c) the effect of asset structure on capital structure, and (d) the effect of sales growth, business risk, and asset structure simultaneously on capital structure. The population in this study are manufacturing companies in the consumer goods industry sector. Sampling was carried out using purposive sampling method. This study uses correlational research. The type of data used is secondary data and the data collection technique used is non-participant observation method. Based on the multiple regression coefficient test, it can be concluded that sales growth (0.013), business risk (0.000), and asset structure (0.000) have an effect on capital structure because the significance value is <0.05. Simultaneously sales growth, business risk, and asset structure have a significant effect on capital structure with a significance value of 0.000 <0.05. Based on the results of the coefficient of determination, it can be concluded that sales growth, business risk, and asset structure have an effect on capital structure of 49.3%. Keywords: Sales growth, business risk, asset structure and capital structure.